Marcial Perozo: the legacy of a cultural heritage to the popular music of Lara state, Venezuela (Mayéutica Revista Científica de Humanidades y Artes, 2022)
All societies have an identity, historical memory and personality that define their past, present and future; sociocultural reality that involves a constant conservation and enhancement of the meanings that these profiles represent. However, it has beenforgotten to raise awareness among the relevance of heritage, and in a special way, the unique intangible heritage, fluctuating between the steps of its integral development. In particular, the "musical capital of Venezuela", is the entity and identity of many cultures and artists who still deserve greater social relevance. In this way, the present work became the main purpose to make an approximation to the biography of Master Marcial Perozo and it’s legacy in the context of larense popular music. The transcript of the information, allowed to approach to an interpretive synthesis where the contribution given in favor of the preservation and communication of the intangible heritage present in the popular musicians of the Lara state.
Keywords: Marcial Perozo; cultural heritage; intangible heritage; popular music larense